Treatment of minimal hepatic encephalopathy - ZHAO Kai (Linchuang Gandanbing Zazhi, 2014)
Minimal hepatic encephalopathy (MHE) is defined as early hepatic encephalopathy without grossly evident neurologic abnormalities, but with cognitive deficits that can be revealed by psychometric testing. However, numerous studies have shown a lack of obvious clinical manifestations in MHE patients, and there is no international unified diagnostic gold standard for this disease. Affected patients′ quality of life and ability to work are markedly impaired, and some even gradually progress to symptomatic hepatic encephalopathy. The treatment methods for MHE mainly include eliminating the precipitating factors for this disease and medication. This review presents the options for treatment of MHE and gives an objective evaluation of the efficacy of each treatment scheme. Currently, several treatment methods are used together, but no studies have demonstrated that combined use of treatment methods can improve the treatment outcome.